Four years' experience of a ROTEM®‐guided algorithm for treatment of coagulopathy in obstetric haemorrhage1. (5th April 2019) - McNamara, H.; Kenyon, C.; Smith, R.; Mallaiah, S.; Barclay, P.
Summary: We report four years of observational data from a large UK hospital and tertiary referral unit, following the introduction of a rotational thromboelastometry‐guided algorithm for treatment of coagulopathy in major obstetric haemorrhage. Fibrinogen concentrate was used to treat acquired hypofibrinogenaemia as defined by a FibTEM A5 value of < 7 mm, or 7–12 mm with ongoing or high risk of haemorrhage. Of 32, 647 deliveries over 4 years, 893 (2.7%) women had an estimated blood loss ≥ 1500 ml. Two‐hundred and three (23%) of these had a FibTEM A5 ≤ 12 mm and 110 received fibrinogen concentrate. We compared clinical outcomes and blood product use with 52 patients who met the same criteria, over a 12‐month pre‐intervention period during which shock packs were used. In the algorithm group, there was a significant reduction in the number of units (p < 0.0001) and total volume (p = 0.0007) of blood products transfused, with a reduction in transfusion‐associated circulatory overload (p = 0.002). Women with placental abruption exhibited more severe coagulopathy and required higher doses of fibrinogen concentrate than women who bled due to other causes. Analysis of rotational thromboelastometry results demonstrated that coagulopathy is not observed in all women who suffer obstetric haemorrhage and cannot be predicted solely by blood loss. Therefore, formulaic treatment with blood products is not justified. When coagulopathy does occur, it appears to be multifactorial and can be severe. Point‐of‐care testing allows early identification and individualised treatment of coagulopathy. This is supported by the improved outcomes reported.